Ecosystem Services in the Light of a Sustainable Knowledge-based Economy - Michałowski, Artur (Problemy Ekorozwoju, 2012)
The article attempts to present the issue of ecosystem services in the light of a sustainable knowledge-based economy. The category of ecosystem services is of key importance in the emerging economy of sustainable development, which analyses the society-economy-environment macro-system. The economic system should be based on knowledge and pursue a new paradigm of sustainable development, with consideration given to ecosystem services. The article examines the most important aspects of sustainable development and the essence of a sustainable knowledge-based economy as theoretical and practical perspectives of outlining the foundations of ecosystem services for the development of society.